Teachers’ digital competence and educational quality in rural vocational schools - Luthfiani, Luthfiani; Rahmah, Alifia Taufika; Madhakomala, Madhakomala (Universitas Jambi, Indonesia, 2026)
Digital technology is increasingly important in vocational education, yet many rural schools continue to face challenges in integrating it into teaching and learning. This study explores how teachers in a rural vocational high school in Tanjung Jabung Barat, Jambi, Indonesia, develop and apply digital competence in their professional practice. A qualitative case study design was used, involving semi-structured interviews with seven school stakeholders and an analysis of relevant school documents. The findings show that teachers encounter a range of challenges, including limited infrastructure, uncertainty in using unfamiliar technologies, and restricted access to sustained professional support. At the same time, teachers who received encouragement from school leaders, collaborated with colleagues, and participated in ongoing learning activities demonstrated greater confidence in using digital tools. The study suggests that digital competence develops through the interaction of personal motivation, workplace support, and opportunities for continuous professional learning. Based on these findings, an integrated framework is proposed that connects technological pedagogical content knowledge (TPACK), human resource development, and digital leadership.